2022
DOI: 10.1037/edu0000530
|View full text |Cite
|
Sign up to set email alerts
|

Data-based decision-making in schools: Examining the process and effects of teacher support.

Abstract: The idea of data-based decision-making (DBDM) at the classroom level is that teachers use assessment data to adapt their instruction to students' individual needs and thus improve students' learning progress. In this study, we first investigate this theoretically assumed DBDM process, and second, we evaluate the effectiveness of teacher support on the different steps of this process. Using longitudinal data of N = 120 teachers and their N = 2458 students, we analyzed the relations between teachers' log-file-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…Förster et al, 2018 ; Müller et al, 2017 ). A rational basis to differentiate and adjust instruction is assessment data on student performance, students’ individual development, and thus their response to instruction (e.g., Förster et al, 2018 ; Hebbecker et al, 2022 ). This places high demands on teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Förster et al, 2018 ; Müller et al, 2017 ). A rational basis to differentiate and adjust instruction is assessment data on student performance, students’ individual development, and thus their response to instruction (e.g., Förster et al, 2018 ; Hebbecker et al, 2022 ). This places high demands on teachers.…”
Section: Discussionmentioning
confidence: 99%
“…We checked the missing data pattern and found that a MCAR pattern could not be reasonably assumed based on Jamshidian and Jalal's two-step procedure (Jamshidian et al, 2014). However, when creating 28 equally sized bins for a simple total score at T1 (i.e., T1 reading performance is statistically controlled to a certain degree), we found that in 78.6% of the bins the MCAR assumption could not be refuted (for a similar approach, see Hebbecker et al, 2022). We thus assume that the data follow a MAR pattern, and that the missing data pattern is most likely more on the MAR side of the continuum of missing data patterns between MAR and MNAR (Graham, 2009;Newman, 2014).…”
Section: Missing Valuesmentioning
confidence: 99%
“…Data-based Decision Making is more dependent on formal data (Wayman et al, 2012;Schildkamp, 2019;Eysink and Schildkamp, 2021;Hebbecker et al, 2022) and generally distinguishes between two types of measures: curriculum-based measurement (CBM) and mastery measures . CBMs are short, standardized measures that indicate the overall skill level.…”
Section: Collecting and Analyzing Data On Pupils' Learningmentioning
confidence: 99%
“…After data collection, an analysis phase is needed to convert the raw data into useful information (Klute et al, 2017;Eysink and Schildkamp, 2021). Data can be presented in many forms: tables, texts or graphs (Hebbecker et al, 2022) When curriculum-based measurements is used, pupils' results can be compared to a pre-established cut-off score or the slope can be analyzed to establish whether progress is in line with expectations Oslund et al, 2021). The aim of this analysis phase is to identify pupils' strengths and weaknesses in order to best meet their needs (Eysink and Schildkamp, 2021).…”
Section: Collecting and Analyzing Data On Pupils' Learningmentioning
confidence: 99%